Penegakan Hukum Tindak Pidana Perjudian Sebagai Mata Pencaharian (Di Kepolisian Resor Kota Pasuruan) - Khusniatul Amallia; Yana Indawati (Pusat Riset dan Inovasi Nasional, 2023)
Gambling games are a crime regulated in article 303 bis of the Criminal Code. Gambling games are often used as a livelihood. Gamblers often make this a livelihood because the lures that are given from gambling games look profitable with only a little money. But this is of course just a ruse so that someone is interested in participating in gambling. Article 303 bis of the Criminal Code has regulated the crime of gambling as a means of livelihood. The Pasuruan City Police Resort is trying to enforce the law on gambling crimes that occurred in Pasuruan City. Along with the development of the era, there are more and more types of gambling crimes. Judging from its history, criminal acts of gambling will always exist and some of the people playing gambling is a customary habit that does not need to be eliminated or even reported to the Police. This of course makes the role of the Police indispensable in informing the public that this gambling game is a crime that needs to be enforced.